Ionic expansive soil modified diaphragm as well as preparation method and application thereof
By using ion-modified expanded clay to modify the separator in a sodium metal battery without a negative electrode, the problem of uneven sodium metal deposition was solved, improving the battery's cycle life and performance at high current density, and enabling high-energy-density battery applications.
Patent Information
- Application Number
- CN202511154935.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2025-12-16
AI Technical Summary
Existing sodium metal batteries without a negative electrode suffer from uneven sodium metal deposition under high current and high capacity conditions, resulting in short cycle life. Furthermore, existing technologies cannot meet the requirements for high reversible efficiency and dendrite-free sodium metal deposition morphology.
The membrane is modified with ion-expansive clay. The coating consists of ion-expansive clay material and polymer binder, with a coating thickness of ≤10μm. By coating the polypropylene or polyethylene membrane with ion-expansive clay material, the uniformity of sodium metal deposition and electrolyte stability are improved.
It improves the coulombic efficiency and cycle performance of sodium metal anode deposition, ensures long-life cycle stability of anode-free sodium metal batteries at high energy density, and improves the dissolution performance of sodium metal deposition at high current density.
Smart Images

Figure CN121149604A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to an ion-type modified diatomite separator and a preparation method and application thereof, and belongs to the technical field of secondary batteries. BACKGROUND
[0002] Traditional lithium ion and sodium ion batteries both rely on ions to be stored in carbon materials, which greatly limits the energy density of the batteries. In recent years, researchers have proposed a new type of negative electrode-free sodium battery, which has only a copper foil or aluminum foil as a current collector on the negative electrode side (i.e., there is no active negative electrode material in the battery), and ions do not flow to the negative electrode, but sodium is deposited in the form of metal on the copper foil or aluminum foil of the negative electrode current collector in situ during the charging process, and is again changed into sodium ions and migrated to the positive electrode during discharging. No dendrites are formed during the charging and discharging process, and therefore, the negative electrode-free sodium metal battery has the advantages of high energy density, low production cost, safe production process and the like.
[0003] The negative electrode-free sodium metal battery only relies on the negative electrode current collector, and no sodium metal is used before the battery is assembled, and the active sodium is entirely from the sodium-containing positive electrode material or the pre-sodiumized material. However, since the negative electrode does not provide active material, the reversibility of sodium metal on the negative electrode current collector is required to be high. The applicant finds that, at present, through the compounding of an ether electrolyte, the coulombic efficiency of sodium metal on the aluminum foil current collector can be ensured to be more than 99%, but the high reversibility and dendrite-free sodium metal deposition morphology under high current and high capacity working conditions cannot be met, which seriously affects the cycle life of the high-energy-density negative electrode-free sodium metal battery. SUMMARY
[0004] Therefore, the application first provides an ion-type modified diatomite separator, which can improve the sodium metal negative electrode deposition and dissolution coulombic efficiency, ensure the long-life cycle stability under the working conditions of the negative electrode-free sodium metal battery, and can be widely applied to the high-energy-density negative electrode-free sodium metal battery system.
[0005] Specifically, the application is realized through the following scheme:
[0006] An ion-type modified diatomite separator, comprising a separator and a coating layer on the separator, wherein the coating layer comprises an ion-type modified diatomite material and a polymer binder, and the mass ratio of the ion-type modified diatomite material to the polymer binder is 80-99:1-20.
[0007] Further, as preferred:
[0008] The thickness of the coating layer is less than or equal to 10 microns. More preferably, the thickness of the coating layer is 2 microns.
[0009] The separator is at least one of a polypropylene (PP) separator and a polyethylene (PE) separator.
[0010] The polymer binder is one or several of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyacrylate emulsion (SBR).
[0011] The applicant also provides a preparation method of the above ion-type modified bentonite diaphragm, using industrial-grade bentonite as raw material, and the steps are as follows:
[0012] Step one, add silane, hydrolysis-condensation to form —Si—(CH2)3—Cl anchor points on the surface of bentonite, and then ion exchange with anhydrous tetrabutylammonium fluoride to generate —Si—(CH2)3—N + (Bu)4F - Intermediate, finally add NaFSI-HCl conjugate acid to perform nucleophilic substitution on F - in the intermediate, so as to convert the fixed anion into weakly coordinated —FSI - At the same time, the exchanged F - is precipitated and removed with excess Ca 2+ , to obtain anion-type bentonite material with —Si—(CH2)3—N + (Bu)4FSI - covalent bond on the surface;
[0013] Step two, mix the anion-type bentonite material with the polymer binder in proportion, add a solvent, and stir to form a uniform coating liquid;
[0014] Step three, use a film scraping method to coat the coating liquid on a polypropylene microporous base film, vacuum filter, roll press, heat set, dry, and obtain the ion-type modified bentonite diaphragm.
[0015] Preferably:
[0016] In step one,
[0017] The silane is 3-chloropropyltriisoxysilane (CPTES), and the anchor point is —Si—(CH2)3—Cl.
[0018] The temperature of hydrolysis-condensation is 65-75°C, and the time length is 2-4h, and the molar ratio of silane to industrial-grade bentonite is 1-1.5:1. More preferably, the molar ratio of silane / montmorillonite surface hydroxyl is about 1.2.
[0019] Ion exchange is carried out under ice bath conditions, and anhydrous tetrabutylammonium fluoride is added in equimolar amount to the hydrolysis-condensation product.
[0020] The amount of NaFSI-HCl conjugate acid added is 2-3 times the molar amount of the intermediate.
[0021] The preparation process is preceded by pretreatment, i.e. before hydrolysis-condensation: the industrial-grade expanded soil is first crushed into nodules, then heated at 250℃ for 120 min; then, the interlayer hydroxyl groups are treated by ultrasonic activation in a mixture of hydrogen peroxide and deionized water for 120 min, then filtered and washed, and vacuum dried; finally, the dry powder is dispersed in an aqueous ethanol solution, and the expanded soil colloid is obtained by ultrasonic-high shear stripping, and the expanded soil colloid is subjected to hydrolysis-condensation with silane. Preferably, the average flake size of the expanded soil colloid is < 500 nm.
[0022] The mass concentration of hydrogen peroxide is 1-2%, and the volume ratio of hydrogen peroxide to deionized water is 1:2.5-3.
[0023] The concentration of the dry powder dispersed in the aqueous ethanol solution is 10-20 g / L, and the concentration of the aqueous ethanol solution is 45-50%.
[0024] In step three,
[0025] The vacuum filtration is carried out at 55-60℃ for 10-15 min.
[0026] The roll pressing and heat setting temperature is 120-130℃.
[0027] The drying is carried out at 70-80℃ for 10-15 h.
[0028] The ion-type expanded soil modified separator is applied to a negative electrode-free sodium metal battery, and the negative electrode current collector, the separator, and the positive electrode sheet are stacked in sequence, and an electrolyte is injected, and the coating side is directly opposite to the negative electrode current collector.
[0029] The construction method of the above-mentioned negative electrode-free sodium metal battery is as follows:
[0030] S1, preparing an ion-type expanded soil modified separator;
[0031] S2, mixing the positive electrode active material, conductive carbon black, and binder uniformly, and coating on the surface of the aluminum foil to obtain a positive electrode sheet;
[0032] S3, stacking the negative electrode current collector, the ion-type expanded soil modified separator, and the positive electrode sheet in sequence, and injecting an electrolyte to obtain a negative electrode-free sodium metal battery.
[0033] In the above-mentioned negative electrode-free sodium metal battery:
[0034] The electrolyte is an organic solvent electrolyte of an electrolyte salt, wherein the organic solvent is at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether, and the electrolyte salt is one or more of sodium tetrafluoroborate, sodium hexafluorophosphate, sodium triflate, sodium bis(oxalato)borate, sodium difluoro(oxalato)borate, sodium difluoro(bisoxalato)phosphate, sodium tetrafluoro(oxalato)phosphate, sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, and sodium perchlorate.
[0035] The positive electrode active material is at least one of sodium iron pyrophosphate, sodium iron sulfate, sodium vanadium phosphate, sodium vanadium fluorophosphate, a layered oxide, Prussian blue, Prussian white, and the like.
[0036] The negative electrode current collector is a carbon-coated aluminum foil or a carbon-coated copper foil.
[0037] Compared with a conventional separator, the ion-type swelling soil material modified separator can synergistically improve the cycle performance of sodium metal deposition and dissolution at a large capacity: on the one hand, the swelling soil material with uniform pores can effectively absorb the constant amount of acidic substances generated in the electrolyte, effectively delaying the degradation of the electrolyte; on the other hand, the anion and other functional groups introduced by modification improve the migration coefficient of sodium ions. Both of the above synergistically promote the uniform and dense deposition and stripping of sodium metal in the charging and discharging process, effectively improving the cycle performance of sodium metal deposition and dissolution at a large capacity. BRIEF DESCRIPTION OF DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings needed to be used in the embodiments or prior art description will be briefly introduced as follows. Obviously, the drawings in the following description are only some embodiments of the present application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0039] Figure 1 Fig. 1 is a structural schematic diagram of a negative electrode-free sodium metal battery of the present application,
[0040] Fig. 1 is a structural schematic diagram of a negative electrode-free sodium metal battery of the present application,
[0041] Figure 2 Fig. 1 is a structural schematic diagram of a negative electrode-free sodium metal battery of the present application,
[0042] Figure 3 Fig. 1 is a structural schematic diagram of a negative electrode-free sodium metal battery of the present application, DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and beneficial effects of the present application clearer, the technical solutions in the embodiments of the present application will be further described in detail below with reference to the accompanying drawings in the embodiments of the present application. It should be understood that the specific embodiments described herein are only used to explain the present application and not used to limit the technical solutions of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of the present application.
[0044] In the following examples, the preparations not specially specified are commercially available.
[0045] Example 1
[0046] The present embodiment provides an ionic swelling soil modified separator and its application in a negative electrode-free sodium metal battery.
[0047] Industrial grade swelling soil is used as raw material, and the steps are as follows:
[0048] Step one, preparation of ionic swelling soil: industrial grade swelling soil is first crushed into nodules, then heat treated at 250℃ for 120min; placed in a mixture of 1% hydrogen peroxide and deionized water (volume ratio 1:3) at 80℃ for 2min stirring treatment to remove impurities and activate interlayer hydroxyl, filter and wash to pH≈7, then vacuum dried; then, the dry powder obtained by drying is dispersed in 50% ethanol aqueous solution at 10g / L, and the swelling soil colloid with an average flake diameter of <500nm is obtained by ultrasonic-high shear combined stripping for 30min, then 3-chloropropyltriisoxysilane (silane / montmorillonite surface hydroxyl molar ratio≈1.2) is added dropwise to the swelling soil colloid, hydrolysis-condensation is carried out at 70℃ for 4h to form —Si—(CH2)3—Cl anchor points on the surface of the swelling soil, and then an equal molar amount of anhydrous tetrabutylammonium fluoride is added dropwise under ice bath conditions to exchange —Si—(CH2)3—N + (Bu)4F - Intermediate, then the F - in it is replaced by a weakly coordinated —FSI - anion by using double-dose NaFSI-HCl conjugate acid to carry out nucleophilic substitution, so that the fixed anion is converted into a weakly coordinated —FSI - , and at the same time, the exchanged F 2+ is precipitated and removed with excess Ca + , so that an ionic swelling soil material with surface covalent bonds and —Si—(CH2)3—N - (Bu)4FSI is obtained.
[0049] Step two, preparation of modified separator: take anionic swelling soil material and PVDF (HFP) respectively according to the mass ratio of 8:2, add them into N-methyl pyrrolidone and stir for 6 h to prepare a uniform coating liquid, use a doctor blade method to coat a 4 μm wet film on one side of a 15 μm thick polypropylene microporous base film, after vacuum extraction and dissolution at 60 ℃ for 15 min, roll and heat set at 120 ℃, and then dry at 80 ℃ for 12 h, to obtain an anionic swelling soil modified separator, and the final coating thickness is about 2 μm.
[0050] Step three, preparation of positive electrode sheet: mix the positive electrode active material sodium iron phosphate pyrophosphate, conductive carbon black and the binder PVDF in a mass ratio of 9:0.5:0.5, and coat them on the surface of an aluminum foil after sufficient stirring, to obtain a positive electrode sheet.
[0051] Step four, battery assembly: stack the carbon-coated aluminum foil negative current collector 3, the anionic swelling soil modified separator 2 and the positive electrode sheet 1 in sequence, with the side of the separator having the coating 21 facing the side of the carbon-coated aluminum foil negative current collector 3, and inject an electrolyte, to obtain a negative electrode-free sodium metal battery.
[0052] Comparative Example 1
[0053] The preparation method of the negative electrode-free sodium metal battery of the present comparative example is as follows:
[0054] Mix the positive electrode active material sodium iron phosphate pyrophosphate, conductive carbon black and the binder PVDF in a mass ratio of 9:0.5:0.5, and coat them on the surface of an aluminum foil after sufficient stirring, to obtain a positive electrode sheet; stack the carbon-coated aluminum foil negative current collector, the unmodified polypropylene PP separator and the positive electrode sheet in sequence, and inject an electrolyte, to obtain a negative electrode-free sodium metal battery.
[0055] Comparative Example 2
[0056] The present comparative example and Example 1 are the same in settings, except that in Step two, the side of the separator having the coating faces the side of the positive electrode sheet.
[0057] The prepared negative electrode-free sodium metal battery is detected, and the results are as follows:
[0058] 1) Detection method or standard: cycle performance test: charge at 1.0C rate to the upper limit cutoff voltage, stand for 30 min; then discharge at 1.0C rate to the lower limit cutoff voltage, stand for 30 min; repeat the above steps 100 times, record and calculate the first cycle discharge specific capacity C1 and the 100th cycle discharge specific capacity C100, and the capacity retention rate is C100 / C1*100%.
[0059] Rate discharge performance test: charge to the upper limit cutoff voltage at 1C current, stand for 30 min; discharge to the lower limit cutoff voltage at 1C current, record the specific capacity C1; stand for 30 min; then charge to the upper limit cutoff voltage at 1C current; stand for 30 min; discharge to the lower limit cutoff voltage at 3C current, record the specific capacity C2; calculate the rate retention rate as C2 / C1*100%.
[0060] 2) Test results: as shown in Table 1.
[0061] Table 1: Performance comparison table of different schemes
[0062]
[0063] In combination Figure 2 , 3 and Table 1, it can be seen that:
[0064] Compared with Comparative Example 1, Example 1 improves the sodium metal negative electrode deposition dissolution coulombic efficiency by modifying the separator, ensures the long-life cycle stability under the working conditions of the negative electrode-free sodium metal battery and the feasibility under the large current density.
[0065] Compared with Comparative Example 2, under the condition that the modified separator is unchanged, the separator modification layer only has good effect on the current collector side, and cannot improve the initial efficiency on the positive electrode side, and can only slightly improve the rate performance.
[0066] Example 2
[0067] The settings of this example and Example 1 are the same, the difference is that in step two, the coating liquid is coated on both sides of the polypropylene microporous base film.
[0068] Example 3
[0069] The settings of this example and Example 1 are the same, the difference is that in step two, the coating thickness is changed, and the coating thickness is replaced by 12 μm, 10 μm, 8 μm, 6 μm, 4 μm and 1 μm respectively.
[0070] The batteries corresponding to the above different coatings and different coating thicknesses were subjected to performance detection, as shown in Table 2, and the results showed that: under the condition that the single-sided coating thickness is unchanged, double-sided coating does not obviously improve the performance of the battery. For the thickness of single-sided coating, it can be considered that it has poor initial coulombic efficiency and capacity retention rate at 6 μm and above, but it has certain improvement for the rate performance; below 6 μm, it has good initial coulombic efficiency and cycle capacity retention rate, and has good improvement for the rate performance, and the performance is best at 2 μm, i.e. Example 1.
[0071] Table 2: Influence of different coating thicknesses
[0072]
[0073] Comparative Example 3
[0074] With CN120149425A as a comparative example, the coating layer of the current collector in the invention is composed of conductive carbon material, metal particles, sodium-based or lithium-based fast ionic conductor, and binder, wherein the conductive carbon material includes point type, line type, and surface type; the metal particles and metal mesh need to remove surface uneven oxides and be oxidized and protected by high-temperature oxygen sintering, and the preparation process is relatively complex. The performance of Example 1 in the invention and Example 1 in the present application are compared as shown in the following table.
[0075] Table 3: Comparative Example 3 and the performance of the scheme of the present application
[0076]
[0077] Compared with Comparative Example 3, the ion-type swelling soil modified separator of the present application gives the corresponding battery a first circle coulomb efficiency as high as 98.9%, and a 100 circle capacity retention rate of 1.0C / 1.0C as high as 96.2%. While Comparative Example 3 can only achieve a 100 circle capacity retention rate of 0.5C / 1.0C of 97.1%. The coating layer preparation process of the present invention is more simple, and at the same time, the negative electrode soft package battery has a higher first circle coulomb efficiency and a close capacity retention rate at a higher charge rate.
[0078] Comparative Example 4
[0079] With CN120261590A as a comparative example, the invention obtains a surface modified aluminum current collector rich in fluorosulfonic acid anion ligands by water bath treatment, changes the aluminum current collector surface crystal face to produce more metalophilic interface, and overall improves the uniformity of sodium metal deposition on the current collector. The performance of the example in the invention and Example 1 in the present application are compared as shown in the following table.
[0080] Table 4: Performance comparison of Comparative Example 4 and the present application
[0081]
[0082] Compared with Comparative Example 4, the ion-type swelling soil modified separator of the present application gives the corresponding battery a first circle coulomb efficiency as high as 98.9%, and a 100 circle capacity retention rate of 1.0C / 1.0C as high as 96.2%, which are obviously superior to Comparative Example 4 in terms of first circle coulomb efficiency and capacity retention rate.
[0083] The above-described embodiments only express several possible implementation manners of the present application, the description is relatively specific and detailed, but it cannot be understood as the limitation of the patent scope of the present application, and the embodiments are not used to limit the protection scope in the claims of the present application. For ordinary skilled in the art, without departing from the concept of the present application, several modifications and improvements can be made, and any equivalent implementation or change made without departing from the present application shall be included in the present application.
Claims
1. An ion-modified expansive soil-modified diaphragm, comprising a diaphragm and a coating on the diaphragm, characterized in that: The coating comprises ion-modified expansive soil material and polymer binder, wherein the mass ratio of ion-modified expansive soil material to polymer binder is 80~99:1~20.
2. The ion-modified expansive soil diaphragm according to claim 1, characterized in that: Coating thickness ≤10μm.
3. The ion-modified expansive soil diaphragm according to claim 1, characterized in that: The binder is one or a mixture of several of sodium carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, and polyacrylate emulsions.
4. A method for preparing the ion-modified expansive soil diaphragm according to claim 1, characterized in that: Using industrial-grade expansive soil as raw material, the steps are as follows: Step 1: Add silane, which hydrolyzes and condenses to form anchor points on the surface of expansive soil. Then, it undergoes ion exchange with anhydrous tetrabutylammonium fluoride to generate an intermediate. Finally, add NaFSI-HCl for nucleophilic substitution with a conjugate acid to obtain surface covalent bonds and —Si—(CH2)3—N. + (Bu)4FSI - Anionic expansive soil materials; Step 2: After mixing the anionic expansive soil material and polymer binder in a certain proportion, add them to the solvent and stir to form a uniform coating liquid; Step 3: Using a scraping method, a coating liquid is applied to a polypropylene microporous base membrane, followed by vacuum filtration, roller pressing for heat setting, and drying to obtain an ion-modified expansive clay diaphragm.
5. The method for preparing an ion-modified expansive soil diaphragm according to claim 4, characterized in that: In step one, the silane is 3-chloropropyltriisooxysilane with an anchor point of —Si—(CH2)3—Cl.
6. The method for preparing an ion-modified expansive soil diaphragm according to claim 4, characterized in that: In step one, the hydrolysis-condensation temperature is 65~75℃, the duration is 2~4h, and the molar ratio of silane to industrial-grade expansive soil is 1~1.5:
1.
7. The method for preparing an ion-modified expansive soil diaphragm according to claim 4, characterized in that: In step one, the ion exchange is carried out under ice bath conditions, with anhydrous tetrabutylammonium fluoride and hydrolysis-condensation products added in equimolar amounts.
8. The method for preparing an ion-modified expansive soil diaphragm according to claim 4, characterized in that: In step one, the amount of NaFSI-HCl conjugate acid added is 2 to 3 times the molar amount of the intermediate.
9. A method for preparing an ion-modified expansive soil-modified diaphragm according to any one of claims 4 to 8, characterized in that, The process before hydrolysis-condensation also includes pretreatment: industrial-grade expansive soil is first pulverized by ductile iron and then heat-treated at 250 ℃ for 120 min; then it is placed in a mixture of hydrogen peroxide and deionized water, and after ultrasonic activation of interlayer hydroxyl groups for 120 min, it is filtered, washed, and vacuum dried; finally, the resulting dry powder is dispersed in an ethanol aqueous solution, and exfoliated by ultrasonic-high shear to obtain expansive soil colloid.
10. An ion-modified expansive clay separator according to claim 1 is applied to a sodium metal battery without a negative electrode, wherein a negative electrode current collector, a separator, and a positive electrode sheet are stacked in sequence and an electrolyte is injected, and one side of the coating faces the negative electrode current collector.
Citation Information
Patent Citations
Negative current collector and preparation method and application thereof
CN120149425A
Aluminum current collector for negative-electrode-free sodium metal battery and preparation method of aluminum current collector
CN120261590A
Cited By
Functional diaphragm for prolonging cycle life of sodium metal non-cathode battery and preparation method of functional diaphragm
CN121367019A
Functional separator for improving cycle life of sodium metal anode-free battery and preparation method thereof
CN121367019B